The Chinese pursuit of happiness : anxieties, hopes, and moral tensions in everyday life - Hsu, Becky Yang, 1975-; Madsen, Richard, 1941- (University of California Press, 2019)
"What is happiness and how can we get it? The way people in China ask and try to answer these universal questions tells a lot about the tensions in Chinese culture and society during the present time of political and economic change. These essays by a team of researchers illuminate the causes of anxiety and reasons for hope in China today. They vividly describe the moral dilemmas experienced in contemporary family life, the rituals of happiness performed in modern weddings, the practices of conviviality carried out in shared meals, the professional tensions confronted by social workers, and the hopes and frustrations shared by political reformers"--Provided by publisher.